Entropy generation and thermal performance of tubular heat exchanger fitted with louvered corner-curved V-baffles - Jayranaiwachira, Nuthvipa; Promvonge, Pongjet; Thianpong, Chinaruk; Skullong, Sompol (My University, 2023)
The current article deals with an experimental study on entropy generation analysis and thermohydraulic performance of a uniform heat-flux tube equipped with louvered corner-curved baffle tape (LCBT). Air was drawn into the inserted tube for the Reynolds number (Re) between 4760 and 29,300. The V-shaped LCBT arranged by V-tip in downstream direction was introduced with three baffle pitch ratios (PR = 1–2) and six louver angles (θ = 0–90°) for a fixed attack angle (α) of 30° and baffle height ratio (BR = 0.25). The impacts of investigated parameters on the thermal enhancement factor (TEF), Nusselt number (Nu), friction factor (f), and total entropy generation (S˙gen′) were examined. The measurements showed that the LCBT with the smallest values of PR = 1, θ = 0° give the largest Nu and f at about 4.4 and 19.2 times above the plain tube values, respectively. However, the greatest TEF around 2.23 was seen for employing the LCBT at PR = 1, θ = 45°. The entropy analysis also showed that the S˙gen′ is found to decline with the increment of PR and θ, whereas the minimal S˙gen′is at PR = 1, θ = 0° for lower Re but at PR = 1, θ = 45° for higher Re. Furthermore, the Nu and f empirical correlations for employing LCBTs were also proposed.
Keywords: Entropy generation; Heat exchanger; Louvered baffle; Thermohydraulic performance; Vortex generator